CNTFET Based Design of Optimized High Frequency VCII and Its Application as Mixed Mode Universal Filter Suitable for VHF Band - Smita Khole; Mousumi Bhanja; Mohammad Faseehuddin; Sadia Shireen; Worapong Tangsrirat (International Journal of Numerical Modelling Electronic Networks Devices and Fields, 2025)
ABSTRACT In this research, Carbon Nanotube Field‐effect Transistors (CNTFETs) are employed in the design of a second‐generation Voltage Conveyor (VCII), an analog block. The aim of this research is to study CNTFETs as an alternative to CMOS for designing high‐frequency and low‐voltage circuits. The complete design procedure for VCII and its two variants, namely, modified VCII (M‐VCII) and VCII minus (VCII−) is presented. This work incorporates variations in the design variables of CNTFETs, including pitch, the number of tubes, and the diameter of carbon nanotubes (CNT). The study explores the impact of these variations on the critical performance parameters of the CNTFETs. The optimal values of the design variables for each transistor are calculated through extensive simulation analysis using the Verilog‐A semi‐empirical Stanford Virtual‐Source Carbon Nanotube Field‐Effect Transistor model. The CNTFET‐based VCII and its variants are optimized and validated at the supply voltage of ±0.9 V. The CNTFET‐based VCII exhibits improved voltage and current bandwidths of 1.4 and 1 THz, respectively. The input/output impedance and power dissipation also validate improvement compared to CMOS implementation. To verify the performance of the proposed VCII and its variants, they are used in the design of a mixed‐mode universal filter (MMUF). The proposed filter is designed for a cut‐off frequency of 79 MHz and consumes 7.368 mW of power. The effects of parameter variations and noise on the VCII design are also discussed.
Keywords: Analog and Mixed-Signal Circuit Design; Advancements in Semiconductor Devices and Circuit Design; Radio Frequency Integrated Circuit Design